Ada, Not ADA. - Moran, Tom (Communications of the ACM, 2015)
A letter to the editor is presented in response to the article "Innovators Assemble: Ada Lovelace, Walter Isaacson, and the Superheroines of Computing" by Thomas Haigh and Mark Priestley from the September 2015 issue.